Analysis of the offensive performance of the semi-final teams in the 2019 Men's Handball World Championship - فقي, ئاوات احمد; كنعان, محمد ابراهيم (Sulaimani Journal for Humanities, 2025)
The importance of research on the analysis of matches in the World Championships in order to assess the level of offensive performance, especially skill correction.The research aims to identify the offensive performance between the World Handball Championship teams for men 2019 and the hypothesis of research there are statistically significant differences in offensive performance between semi-finals World Handball Championship For the men, the researchers used the descriptive approach in the survey method.The researchers identified the original research community, the teams of the World Cup teams who reached the semi-finals and the number They are (4) Denmark, Norway, France and Germany) and the number of players of each team (16) players, the total number of players (64) players and the researchers used the standardized observation form used by the (International Handball Federation) and after obtaining the results were statistically processed and reached the following conclusions : There is a successful implementation of seven-meter throws among all teams participating in the semi-finals World Championships. Low scoring rate in the rapid attack organized among all the teams participating in the semi-finals World Championship.